Diastereomeric stilbenoid glucoside dimers from the rhizomes of Gnetum africanum. (October 2020) - Gabaston, Julien; Buffeteau, Thierry; Brotin, Thierry; Bisson, Jonathan; Rouger, Caroline; Mérillon, Jean-Michel; Waffo-Téguo, Pierre
Graphical abstract: Highlights: The stilbenoids were isolated from the rhizome of Gnetum africanum . Separation was performed by centrifugal partition chromatography and Prep. HPLC. Structure was investigated by NMR, vibrational- and electronic- circular dichroism. Isolated stilbenoids have been tested for their iron chelating activity. Two novel diastereomeric stilbenoid glucosides were discovered. Abstract: In a continuing search for neuroprotective stilbenoids, two uncommon diastereomeric stilbenoid glucosides, africanoside A (1 ) and B (2 ) as well as fifteen known stilbenes, E -resveratrol, E -gnetifolin E, E -piceid, E -resveratroloside, E -gnetifolin K, E -gnetol, E -isorhapontigenin, E -isorhapontin, E -isorhapontigenin-4′- O -glucopyranoside, E -gnetin C, E -bisisorhapontigenin B, E -gnemonoside A, E -gnemonoside C, E -gnemonoside D, and E -gnetin E, were isolated from rhizomes of Gnetum africanum, using a combination of centrifugal partition chromatography and preparative HPLC. The structure of these two stilbenoids was investigated by NMR, vibrational circular dichroism (VCD), and electronic circular dichroism (ECD) experiments. The absolute configurations of 1, and 2 were established by VCD as (7a S, 8a S ) and (7a R, 8a R ), respectively. Compound 1 significantly chelated Fe(II) at 100, 250 and 500 μM. The ability of stilbenoids to chelate ferrous ions which are implicated in physiopathological hallmark of Alzheimer's disease provides useful data for potential treatment.